Chitosan-Based Nanogels Designed for Betanin-Rich Beetroot Extract Transport: Physicochemical and Biological Aspects - Silva Nieto, Ramon (2023)
Nanotechnology has emerged as a possible solution to improve phytochemicals’ limitations. The objective of the present study was to encapsulate beetroot extract (BR Ext) within a chitosan (CS)-based nanogel (NG) designed via ionic crosslinking with tripolyphosphate (TPP) for betanin (Bet) delivery, mainly in the ophthalmic environment. BR Ext is rich in betanin (Bet) according to thin layer chromatography (TLC), UV-visible spectroscopy, and HPLC analysis. NG presented a monodisperse profile with a size of 166 ± 6 nm and low polydispersity (0.30 ± 0.03). ζ potential (ζ-Pot) of +28 ± 1 is indicative of a colloidally stable system. BR Ext encapsulation efficiency (EE) was 45 ± 3%. TEM, with the respective 3D-surface plots and AFM, showed spherical–elliptical-shaped NG. The BR Ext release profile was biphasic with a burst release followed by slow and sustained phase over 12 h. Mucoadhesion assay demonstrated interactions between NG with mucin. Moreover, NG provided photoprotection and pH stability to BR Ext. FRAP and ABTS assays confirmed that BR Ext maintained antioxidant activity into NG. Furthermore, in vitro assays using human retinal cells displayed absence of cytotoxicity as well as an efficient protection against injury agents (LPS and H2O2). NGs are a promising platform for BR Ext encapsulation, exerting controlled release for ophthalmological use.